Cycle Slip Detection in Single Frequency GPS Carrier observations using expected Doppler shift - Cederholm, Peter; Plausinaitis, Darius (Nordic Journal of Surveying and Real Estate Research, 2014)
The article presents a case study of cycle slips detection in double differenced L1 carrier phase observations collected with two low–cost single frequency GPS receivers operating in both static and kinematic mode. The receivers deliver half–cycle carrier phase observations. Cycle slips are identified using expected Doppler shift. Expected Doppler shift is computed from the positions and the velocities of the satellites and the receivers. A static and a kinematic experiment are carried out. In the static experiment both GPS receivers are stationary while data are collected, whereas one receiver is mounted on a moving car in the kinematic experiment. In the static experiment, cycle slips with a magnitude of 0.5 cycle are easily detected. In this case the positions of the receivers are estimated from collected code observations, and the velocities of the receivers are zeros as they are stationary. In the kinematic experiment, the positions of the receivers are again estimated from code observations, and the velocities of the receivers are estimated from collected Doppler shift observations. The accuracy of the estimated velocities is so poor that the expected Doppler shift does not make it possible to detect cycle slips with a magnitude of 0.5 cycle. Cycle slips must have magnitudes of several cycles in order to be safely identified. Computer simulations indicate that the velocities should have a standard deviations of 0.05 m/s or less in order to detect 0.5 cycle slips.